Is conventional wisdom about resource taxation correct? Mining evidence from transparency reporting. (October 2021) - Adebayo, Eric; Lashitew, Addisu A.; Werker, Eric
Highlights: We measure and analyze the "government take" in gold mining projects. We develop a theoretical model with a globally competitive mining industry to determine the optimal government take. Data analysis shows that country risk is positively associated with government take, the opposite of the model prediction. Political economy variables have predictive power in determining the government take. Abstract: This paper theoretically and empirically investigates the factors that determine the government "take" in gold mining projects around the world. We develop a theoretical model to predict the government take, which we define as the ratio of total payments to the government from a mining project (including taxes, fees, and royalties) relative to the mining company's pre-tax net revenue from the same project. In line with investment decision theory, our model predicts that governments should decrease their take on mining operations to compensate multinational corporate investors for increased local development costs and political and macroeconomic risk. However, our empirical investigation shows that higher country risk is actually associated with greater government take. Extending the model, we find that political economy variables have as much predictive power in explaining the government take as the basic investment theory model.